Meridional circulation dominates the record-breaking “Dragon Boat Water” rainfall over south China in 2022 - Cheng, Jianbo; Zhao, Yuheng; Zhi, Rong; Feng, Guolin (Frontiers in Earth Science, 2023)
During the "Dragon Boat Water" season in 2022, record-breaking anomalous rainfall occurred over South China (SC). In this study, the causes of anomalous rainfall are investigated by using the novel moisture budget equation of three-pattern circulations. The results show that the anomalous rainfall over SC caused by the horizontal, meridional, and zonal circulations was –10 mm, 168 mm, and 45.3 mm, which contribute –5%, 86%, and 23% of the actual rainfall anomaly (195.1 mm), respectively, suggesting that the meridional circulation contributes most to anomalous rainfall, followed by zonal circulation, and horizontal circulation contributes negatively. Further analysis based on the three-pattern decomposition of the global atmospheric circulation shows that the spatial configuration of the anomalous horizontal circulation and vertical vorticity provides the background for generating the anomalous divergence and convergence of meridional and zonal circulations and further anomalous vertical velocity of the meridional and zonal circulations, ultimately resulting in anomalous rainfall.